Removal of basic brown 16 from aqueous solution using durian shell adsorbent, optimisation and techno-economic analysis - Gopalakrishnan Y.; Al-Gheethi A.; Malek M.A.; Azlan M.M.; Al-Sahari M.; Radin Mohamed R.M.S.; Alkhadher S.; Noman E. (MDPI, 2023)
activated carbon; adsorption; aqueous solution; chemical oxygen demand; concentration (composition); dye; optimization; pollutant removal; reduction; wastewater treatment; Cucumis melo var. inodorus; Durio zibethinus